Turbulence Modeling Using Z-F Model and RSM for Flow Analysis in Z-SHAPE Ducts - Mohammed Karbon; Ahmad K. Sleiti (Journal of Engineering)
Turbulent flow in Z-shape duct configuration is investigated using Reynolds stress model (RSM) and ζ-f model and compared to experimental results. Both RSM and ζ-f models are based on steady-state RANS solutions. The focus was on regions where the RSM has over- or underpredicted the flow when compared to the experimental results and on regions where there are flow separations and high turbulence. The performance of predicting the flow reattachment length in each model is studied as well. RSM has shown the mean flow velocity profile results match reasonably well with the experiment. Advanced ζ-f turbulence model is introduced as user-defined function (UDF) code and applied to the Z-shape duct. It is found that the turbulent kinetic energy production in ζ equation is much easier to reproduce accurately. Both mean velocity gradient and local turbulent stress terms are also much easier to be resolved properly. The current research has found that not only ζ-f model takes less time to complete the simulation but also the mean flow velocity profile results are in better agreement with the experimental data than the RSM although both are coupled steady-state RANS. ζ-f model numerically resolved both the flow separation and reattachment regions better than the RSM. The current numerical results from ζ-f model are attractive and encouraging for wall-bounded flow applications where flow separation and flow reattachment are important for the flow mechanism.